Pemberdayaan Usaha Mikro Kecil Menengah (UMKM) Berbasis Digital di Kelurahan Karawaci Kota Tangerang - Suryatman, Arif Ginanjar; Suryatman, Tina Hernawati (Yayasan Daarul Huda Kruengmane, 2025)
The impact of the rapid development of information and communication technologies affects various activities in human life, one of the affected is the Micro, Small and Medium Enterprises (MSMEs) sector, in sustaining and developing businesses becoming better must utilize technology . The issue that arises at the moment many of the MSME actors still have minimal knowledge in terms of technology. The purpose of this service to the community is to improve digital literacy by providing training to MSME actors in terms of utilization of communication information technology. The method of service to the community is through training to SME performers in Karawaci Village Karawaci District Tangerang City along with the activities of Real Work Lecture. As a result of the training activities participants understood and could practice marketing through electronic media, which was subsequently conducted accompaniment for one week post training.